CAPM regularities for the Athens Stock Exchange - Καρανίκας, Ευάγγελος (SPOUDAI Journal of Economics and Business, 2000)
The cross-sectional relationship between firm-specific characteristics and average stock returns has attracted a significant amount of attention in the financial literature, especially in the U.S. Because these patterns are not explained by the CAPM, they are called CAPM regularities or anomalies. This paper provides evidence on the role of size, book-to-market ratio and dividend yields on average stock returns in the ASE for the period from January 1991 to March 1997. Following Fama and MacBeth's cross-sectional regression methodology enhanced with Shanken's adjustments for the Errors In Variables problem, a statistically significant positive relationship between the book-to-market ratio, dividend yield and average stock returns is reported. The market capitalisation variable ("size effect") does not seem to explain a significant part of the variation in average returns.